2020
DOI: 10.1021/acsmaterialslett.0c00042
|View full text |Cite
|
Sign up to set email alerts
|

Charting the Metal-Dependent High-Pressure Stability of Bimetallic UiO-66 Materials

Abstract: In theory, bimetallic UiO-66(Zr:Ce) and UiO-66(Zr:Hf) metal-organic frameworks (MOFs) are extremely versatile and attractive nanoporous materials as they combine the high catalytic activity of UiO-66(Ce) or UiO-66(Hf) with the outstanding stability of . Using in situ highpressure powder X-ray diffraction, however, we observe that this expected mechanical stability is not achieved when incorporating cerium or hafnium in . This observation is akin to the earlier observed reduced thermal stability of UiO-66(Zr:Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 66 publications
4
21
0
Order By: Relevance
“…106 In a different study, the onset pressure where amorphization occurs was studied as a function of metal node composition in UiO-66(Ce/Zr) and UiO-66(Hf/Zr) via experiment and computation, showing that cerium-based UiO-66 materials have lower mechanical stability compared to their Zr and Hf analogs; see Figure 4. 23 Likewise, and in agreement with previous studies, a large impact of defects on the mechanical stability of UiO-66 based materials was found. Therefore, the increase in catalytic activity through both catalytically active defects and cerium reduces the frameworks' mechanical stability, which agrees with trends in thermal stability.…”
Section: ■ Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…106 In a different study, the onset pressure where amorphization occurs was studied as a function of metal node composition in UiO-66(Ce/Zr) and UiO-66(Hf/Zr) via experiment and computation, showing that cerium-based UiO-66 materials have lower mechanical stability compared to their Zr and Hf analogs; see Figure 4. 23 Likewise, and in agreement with previous studies, a large impact of defects on the mechanical stability of UiO-66 based materials was found. Therefore, the increase in catalytic activity through both catalytically active defects and cerium reduces the frameworks' mechanical stability, which agrees with trends in thermal stability.…”
Section: ■ Introductionsupporting
confidence: 91%
“…Here we would like to emphasize that existing high-pressure structural studies have shown that all the different chemical aspects of MOFs together define the pressure responsive properties, i.e. topology, 13,14,141 porosity, 74 linker length, 74,89 metal-node chemistry, 23,106,163 and the presence of defects. 107 The chemical diversity of MOFs provides a unique material platform to validate existing principles and to identify new guidelines and potentially new unexpected properties.…”
Section: ■ Introductionmentioning
confidence: 98%
“…While numerous reports support the notion that changes to the organic linker [21][22] and topology [23][24] can impact the compressibility of MOFs, systematic studies into the effect of changes to the metal node are less prevalent. 25 Herein, we investigate the role of the metal-carboxylate bond in the compression of UiO-66 by varying the identity of the metal node from Zr-UiO-66 to Hf-UiO-66 and Ce-UiO-66. By keeping the topology, linker, and experimental conditions constant, we isolate the coordination bond as the single structural variable that changes in this series of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…2B-2F). As shown in the spectra of the UiO-66-CdTe core, the typical Zr 3d, Cd 3d, Te 3d, O 1s and C 1s peaks were noted at 179.7, 402.2, 569.8, 529.2 and 284.8 eV, respectively 28 . In the spectra of the UiO-66-CdTe@ZIF-8 CSNCPs, there was a weak signal attributed to Zn 2p suggesting that ZIF-8 shell was successfully attached to the UiO-66-CdTe core.…”
Section: Discussionmentioning
confidence: 90%